Boosting Diagnostic Accuracy of Prostate Cancer: Combining Clinical PSA Level and a Pair of NIR Fluorescent Probes for SLC39A1 and PSMA - Xiuzhu Huo; Fei Yang; Hong Wang; Jiao Chen; Mengyao She; Li Xue; Ping Liu; Shengyong Zhang; Jianli Li (Angewandte Chemie, 2026)
ABSTRACT Prostate cancer (PCa) is a leading malignancy in men globally. Although serum prostate‐specific antigen (PSA) testing is prevalent for PCa screening, its inherent limitation in specificity and sensitivity frequently leads to high false‐positive and false‐negative diagnoses. To address this challenge, we present a PSA+ strategy that integrates a clinically defined PSA threshold (10 ng/mL) with a pair of complementary near‐infrared (NIR) fluorescent probes: a zinc‐complex‐based probe (Cy‐O‐NS‐a‐Zn) targeting the zinc transporter solute carrier family 39 member 1 (SLC39A1), and a glutamate‐urea‐lysine (Glu‐Urea‐Lys) ligand‐based probe (Cy‐S‐Glu) targeting prostate‐specific membrane antigen (PSMA). This combinatorial approach accurately discriminates PCa from normal prostate cells, delineates tumor margins in patient‐derived xenograft (PDX) mouse models with robust tumor‐to‐background ratios (TBR), and enables fluorescence‐guided surgery. Importantly, a double‐blind histopathological validation using 70 cases of human prostate tissue specimens revealed that the PSA+ strategy substantially outperformed PSA testing alone, improving diagnostic specificity from 70% to 97.6% and sensitivity from 75% to 96.8%. Collectively, this work provides a rapid, accurate, and comprehensive diagnostic paradigm that complements standard PSA testing, thereby refining clinical diagnosis and decision‐making in PCa.